Glass Transition and Crystallization in Hexagonal Boron Nitride: Crucial Role of Orientational Order. Issue 2 (18th November 2019) - Ravinder, R.; Garg, Prateet; Krishnan, N. M. Anoop
Abstract: While extensive studies have been carried out on 2D crystals, their disordered counterpart, namely 2D glasses, remain poorly explored. Using molecular dynamics simulation, it is demonstrated that hexagonal boron nitride (h‐BN) can exhibit crystallization and glass transition. Similar to archetypical glasses, it is observed that the glassy structures are disordered, marked by the absence of any long‐range order while exhibiting some short‐range order. Further, the structures obtained are stable in three dimensions, confirming the realistic nature of the 2D glasses. Interestingly, it is observed that the orientational order of the h‐BN structure with respect to density as well as ground state enthalpy follows a master curve for both crystallization and glass transition, revealing thermally accessible regions for the structure. Further, the standard deviation of orientational order provides information about the spatial heterogeneity in the structure, the rearrangement of which results in the formation of crystal/glass. This suggests that the orientational order may play a crucial role in controlling the propensity for crystallization/glass transition in systems having directional bonds. Abstract : Despite extensive studies on 2D crystals, their disordered counterpart remains poorly explored. Using atomistic simulations, the disordered structures formed by melt‐quenching of 2D hexagonal boron nitride are analyzed. It is shown that the degree of disorder is controlled by the thermal history. Further, the orientational order represents the spacial heterogeneity and provides the thermally accessible configurations of the system.